Prospective Plans To Improve Uzbekistan's Position In International Logistics And Increase Its Efficiency (Open Academia: Journal of Scholarly Research, 2024)
In this research work, the essence of the logistics efficiency index, the place of Uzbekistan in the logistics efficiency index, the state of the logistics efficiency index indicators in recent years have been analyzed, as well as the implementation of scientific research in these areas of activity, the analysis of problems and proposals for elimination are given